Improving the use of research evidence in guideline development: 2. Priority setting - Oxman, Andrew D.; Schünemann, Holger J.; Fretheim, Atle (Health Research Policy and Systems, 2006)
The World Health Organization (WHO), like many other organisations around the world, has recognised the need to use more rigorous processes to ensure that health care recommendations are informed by the best available research evidence. This is the second of a series of 16 reviews that have been prepared as background for advice from the WHO Advisory Committee on Health Research to WHO on how to achieve this.